Comparação de dois diluidores na fertilidade de éguas inseminadas com sêmen asinino a fresco ou resfriado. - Raissa Rossi (2008)
The objectives of this study were evaluate a) two diluters: skim milk-glucose (TI) and egg yolk-glicin (TII) on mares fertility inseminated with diluted jackass fresh semen (EI), or diluted and cooled at 5oC, for 12 hours (EII); b) the fertility of different Pêga jackassess; c) the incorporating of a reproductive management, arranger for artificial insemination (AI) three times per week and d) the variables: Interval AI/ovulation, the number of inseminations, mare reproductive status and effect of age on mares fertility in EII. 67 and 141 mares were used in EI and EII, respectively, without a breed definition, being uniformly distributed in two groups (TI and TII). Semen was collected from five sexually mature jackasses (J1, J2, J3, J4 e J5). After being collected, the semen was diluted in TI and TII and used until 30 minutes after being collected (EI), or after being cooled (EII). The mares were inseminated every Tuesday, Thursday and Saturday, since they have one follicle of 3.0 to 3.5 cm of diameter until the ovulation. The pregnancy was detected using rectal palpation, a regular use of teasers and ultra-sonography made on a regular interval of 14 days. The conception/cycle rates were 57.89 and 36.21% for J1; 35.71 and 43.75% for J3; 56.25 and 46.30% for J4 and 71.43 and 74.47% for J5, in EI and EII, respectively. There was superiority (p<0.05) of J5 in EII. The diluters did not affect (p>0.05) the conception rate obtained by mares inseminated in EI or in EII. The jackasses used were different about seminal characteristics and mares fertility. The cooled semen kept functional for 60 hours, inside the mares genital tracts. The variables studied did not affect (p>0.05) the fertility. It was concluded that the proposed reproductive management is feasible due to the fertility results